(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Infantile spasms (epileptic spasm) is an epileptic encephalopathy with unique clinical and electrographic features, which affects children mostly in the middle of the first year of life. Objective: The aim of this study was to evaluate the clinical and electroencephalographic profile and short-term outcome in infantile spasm. Methodology: This was a randomized controlled trial study done in Department of Pediatric Neurology, National Institute of Neuroscience & Hospital, Dhaka, Bangladesh. The patient of infantile spasm aged 2 months to 2 years were enrolled in the study from June 2017 to May 2018. With parent’s written informed consent, they were randomized into two groups, 25 in each. One group got ACTH only and another group got both ACTH and vigabatrin. Detailed history including seizure pattern was taken. EEG was done before and after2 -3 weeks of starting treatment. They were followed up at 8, 15, 43 days. Results: The mean age of onset of seizure (mean ±SD) was 7.24±4.13 (2 to 19) month on hormonal therapy and 6.84±5.89 (2 to 22) month on combination therapy. Most patient had history of perinatal birth asphyxia, developmental delay, seizure pattern was flexor spasm and EEG pattern were predominantly classical hypsarrhythmia in both groups. After treatment cessation of spasms occurred between 14 to 42 days in 72.0% in combination therapy and 44% in hormonal therapy (P value=0.045). EEG became normal in 60.0% and 32.0% patients in combination and hormonal therapy respectively (P value =0.047). Conclusion: In conclusion combination therapy of ACTH hormone plus vigabatrin has better than ACTH therapy alone in cessation of clinical spasms and electroencephalographic remission. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):130-135